How to show this equation below is true.

$$\sum_{n\leq x}d(n)=\sum_{ab\leq x}1$$

$d(n)$ is the divisior function. It seems easy but i just can't see it.


Just modify the sums slowly, for example from right to left:

$$\sum_{ab\le x} 1 = \sum_{n\le x} \sum_{ab=n} 1 = \sum_{n\le x} \sum_{a \mid n} 1 =\sum_{n\le x} d(n).$$


Let $X=\{(a,b)\mid ab\leq x\}$, let $X_n=\{(a,b)\mid ab=n\}$.

Show that $$X=\bigcup_{n\leq x} X_n$$ and that the $X_n$ are disjoint.

Then the right hand side is $|X|$ and the left hand side is $\sum_{x\leq n} |X_n|.$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.